Alasan Pemberatan Hukuman dalam Tindak Pidana Memproduksi dan Mengedarkan Obat Tanpa Izin Edar di Kabupaten Kupang: Putusan No. 58/Pid.Sus/2020/Pn. Olm - Adrianty Charmelita Valentine Mali; Deddy. R. CH. Manafe; Rosalind Angel Fanggi (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Health is a state of health, both physically, mentally, spiritually and socially that allows everyone to live productively socially and economically. Health is based on legal provisions, including health law. The development of criminal acts in the field of health sciences One of the crimes in health law that is rampant is the crime in the field of pharmacy, one of which is circulating pharmaceutical preparations of drugs without a distribution permit. Drugs without a distribution permit cannot be freely traded to the public. This is not without reason, unlicensed drugs must be consumed in the right dosage so as not to endanger the health of the public or the people who consume the drug. This research is a normative juridical research using secondary data through literature studies, namely by using research on various sources of books, laws and regulations related to the crime of producing and distributing pharmaceutical preparations without a distribution permit. From the research conducted, it can be concluded that the application of criminal sanctions against criminal offenders who circulate pharmaceutical preparations without a distribution permit is contained in several laws and regulations, namely, Law No. 17 of 2023 concerning Health and Law No. 36 of 2009 concerning Health as a means of crime prevention. The implementation of this law is expected to ensnare the perpetrators of the crime of distributing pharmaceutical preparations without a distribution permit.